Sekolah Kebangsaan Batu Tiga portal - Muhamad Nor Zakwan, Che Ali (2014)
Previously, Sekolah Kebangsaan Batu Tiga has had the school system, the system is developed using Joomla as a platform for information about the school and also delivers information. However, the system did not last long when having problems and the system is already removed by the school. Besides that, the selected web-based application system to establish Sekolah Kebangsaan Batu Tiga. This is one of the website that also provides information from a variety of sources and it is also a process to simplify every management of the school. The system uses a technique of waterfall model as the implementation steps to complete the portal system. Besides that, the portal has two types which users and user admin the different character, user as the reader information and admin as the person in charge of portal. The system used software Adobe Dreamweaver as the programming language and MySQL as the database for the system.